Enabling a diversity-oriented catalytic atom looping of a biobased polycarbonate - Lanaro, Enrico; Senthamarai, Thirusangumurugan; Hashmi, A. Stephen K.; Kleij, Arjan W. (ChemSusChem, 2025)
Herein, it is demonstrated that biobased poly(menthene carbonate) (PMC) can be conveniently used to enable catalysis-promoted atom looping thereby creating functionalized synthons and new types of repolymerizable monomers. The biobased polycarbonate undergoes chemoselective depolymerization in the presence of a bicyclic guanidinium providing under distinct reaction conditions and concentrations high-yield and selective access to either menthene oxide (MO), menthene carbonate (MC), or menthene diol (MD). These latter depolymerization products further enable the valorization of the original polymer atoms into several functionalized, partially biobased building blocks by integrating a monomer-and-molecular loop approach. As a proof-of-principle, four distinct scaffolds were converted into novel (bifunctional) monomers with potential to create a wider series of macromolecules. This work exemplifies a unique and holistic catalytic reuse of polymer atoms accommodating an on-demand preparation of fine-chemical precursors, repolymerizable monomers, and new monomer precursor designs.
Gesehen am 30.01.2026